BANCO DE TUTORIALES PEDAGÓGICOS PARA FORTALECER LA ACTIVIDAD ACADÉMICA VIRTUAL EN LOS ESTUDIANTES DEL DÉCIMO AÑO EGB EN LA UE ECUADOR, BABAHOYO. - FLORES ABRIL JOSÉ LUIS (2021)
The objective of the work developed is to propose a bank of pedagogical tutorials to strengthen virtual academic activity in students of the tenth year of EGB at the U E Ecuador, Babahoyo. The work has a quantitative-qualitative approach methodology, applying a descriptive, explanatory study with a non-experimental approach. The population was made up of students of the tenth year EGB of the EU Ecuador, likewise for the sample the total population was considered, which are the 60 students of the tenth years, to whom the survey technique was applied using the questionnaire as a tool. In the result stage, there is the validation of the surveys and the verification of the hypothesis, for this the chi-square method was used, using the observed and expected frequencies, to conclude with a decision rule which accepts the hypothesis. The conclusions show that tutorial banks are a program required to generate a synergistic activity in the teaching-learning process in students, being accessible, easy to use and interactive, and the impact that is perceived on students was verified. who participate less in their classes, thus allowing students to be always focused on their studies. The recommendations suggest actions such as socializing the tutorials to students and encouraging teachers of all subjects to implement the inherent use of tutorial videos as part of their academic activities.